Mechanisms, roles and consequences of governance emerging issues - Gnan, Luca.; Hinna, Alessandro; Monteduro, Fabio (Bingley, U.K. : Emerald, 2014)
This 2nd volume of the series builds on the themes of volume 1. Established concepts and theoretical issues are presented by established scholars in the governance, management and administration fields. These are set alongside highlighted emerging themes, and they're practicality illustrated through specific case examples.
Advancing public governance research : individual and collective dynamics in and around the boardroom / Alessandro Hinna ... [et al.] -- Governing public value : how to foster knowledge-intensive collaboration in the public sector / Michèle Morner, Manuel Misgeld -- Financial Performance in Indian state owned enterprises following corporate governance reforms / Stuart Locke, Geeta Duppati -- The development of the governance of regulatory networks: the case of the European telecommunications regulatory network / Angel Saz-Carranza, Francisco Longo, Susanna Salvador Iborra -- Empirical research on non-profit boards : main features and differences from the literature on corporate and public boards / Sonia Moi, Fabio Monteduro, Luca Gnan -- What drives good philanthropy? The relationship between governance and strategy in foundations / Giacomo Boesso, Fabrizio Cerbioni, Kamalesh Kumar -- Transfer to transform. Leveraging firm's knowledge to mold corporate foundation's effectiveness / Marco Minciullo, Matteo Pedrini -- Volunteer management and measurement systems for Italian voluntary organisations / Laura Berardi, Michele A. Rea.
Print version record
Keywords: Political Science -- Public Policy -- General; Political Science -- General; Politics & government; Non-profitmaking organizations; Corporate governance